2007
DOI: 10.1074/jbc.m611831200
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis thaliana Squalene Epoxidase 1 Is Essential for Root and Seed Development

Abstract: Squalene epoxidase converts squalene into oxidosqualene, the precursor of all known angiosperm cyclic triterpenoids, which include membrane sterols, brassinosteroid phytohormones, and non-steroidal triterpenoids. In this work, we have identified six putative Arabidopsis squalene epoxidase (SQE) enzymes and used heterologous expression in yeast to demonstrate that three of these enzymes, SQE1, SQE2, and SQE3, can epoxidize squalene. We isolated and characterized Arabidopsis sqe1 mutants and discovered severe de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
109
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(126 citation statements)
references
References 54 publications
9
109
0
Order By: Relevance
“…Squalene epoxidase can carry out two successive epoxidations, performing the mirror image epoxidations of both the 2,3 and 22,23 end positions of the squalene molecule. Di-epoxidation of squalene by squalene epoxidase has been reported in numerous triterpenoid synthase systems (25)(26)(27)(28)(29), and plant squalene epoxidases have been functionally expressed and shown to yield both mono-and di-oxidosqualene (30,31). Modeling of the SgSQE protein supports di-epoxidation and indicates that the presence of the first epoxy oxygen does not hinder the docking for the second epoxidation (SI Appendix, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Squalene epoxidase can carry out two successive epoxidations, performing the mirror image epoxidations of both the 2,3 and 22,23 end positions of the squalene molecule. Di-epoxidation of squalene by squalene epoxidase has been reported in numerous triterpenoid synthase systems (25)(26)(27)(28)(29), and plant squalene epoxidases have been functionally expressed and shown to yield both mono-and di-oxidosqualene (30,31). Modeling of the SgSQE protein supports di-epoxidation and indicates that the presence of the first epoxy oxygen does not hinder the docking for the second epoxidation (SI Appendix, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, it has recently been reported that, in Arabidopsis thaliana, squalene epoxidase (Erg1 in budding yeast), a major enzyme of the sterol biosynthetic pathway that depends on Ncp1 and Cbr1 (Fig. 8), regulates the polarized growth of roots and hypocotyl (Rasbery et al, 2007).…”
Section: Erg4 Ncp1 and Cbr1 Have Overlapping Functions With Ste20 Anmentioning
confidence: 99%
“…Then it was discovered in fungi as an enzyme taking part in ergosterol synthesis and in plants, where it is a part of phytosterols synthesis pathways (Petranyi et al , 1984 ;Godio et al , 2007 ;Rasbery et al , 2007 ;Uchida et al , 2007 ;He et al , 2008;Han et al , 2010 ). SE was also identifi ed in some bacteria which produce pentacyclic triterpens instead of sterols, so-called hopanoids synthesized from squalene by squalene-hopene cyclase (SHC) (EC 5.4.99.17) (Nakano et al, 2003;Pearson et al , 2003 ;Volkman , 2003 ;Nakano et al , 2007 ).…”
Section: Introduction: Squalene Monooxygenasementioning
confidence: 99%